Strategic Framework for Regional Development based on Potential Sectors and Investment in Central Kalimantan - Muhammad Usman Farikh Ramadhan; Muhammad Arif (Universitas Muhammadiyah Surakarta, 2025)
This research investigates the significance of the tourism industry within the economic framework of Central Kalimantan Province and its intersectoral linkages using input–output analysis. The tourism sector is represented by subsectors responsible for the provision of accommodation and food services, as reflected in the 2016 Input Output Table of Central Kalimantan Province. The data utilized in this study were obtained from secondary sources published by the Central Statistics Agency (BPS). The findings reveal that the accommodation and food services sector exhibits a backward linkage coefficient of 1.4318 and a forward linkage ratio of 0.9379. These results indicate that the tourism industry maintains strong backward linkages, while its forward linkages remain relatively modest. Overall, the analysis highlights that the tourism sector in Central Kalimantan holds considerable potential for development through increased investment and targeted policy interventions. Strengthening interregional connectivity, improving essential infrastructure, and simplifying tourism investment procedures are key strategies to enhance the sector's contribution to economic growth and sustainable regional development.